Chitinase-3-Like Protein 1 (YKL-40) Reflects the Severity of Symptoms in Atopic Dermatitis - Salomon, Joanna (J Immunol Res, 2017)
Chitinase-3-like protein 1 (YKL-40) is suggested to be associated with type 2 T helper response and atopy. The aim of the study was the evaluation of serum YKL-40 level in atopic dermatitis. The study was performed on 59 patients: 27 males and 32 females, aged from 18 to 64 years. The severity of the disease was assessed by the SCORAD and objective SCORAD indexes. The severity of pruritus was measured by the visual analogue scale. Blood samples were taken to examine serum level of YKL-40, total IgE level, C-reactive protein level, white blood cell count, and neutrophil count. YKL-40 serum levels were significantly higher in patients with atopic dermatitis compared to the controls. There was a positive correlation between YKL-40 concentration and SCORAD, objective SCORAD, and pruritus. This study has shown that YKL-40 serum level is increased in patients with atopic dermatitis and reflects the severity of symptoms.